Anatomical And Physiological Features And Ultrasonic Diagnostics Of The Hepatobiliary System (Literature Review). (Eurasian Research Bulletin, 2025)
The review systematizes modern data on the anatomical and physiological features of the hepatobiliary system in individuals of different ages, sexes and somatotypes. The article considers the morphological and functional characteristics of the liver, gallbladder and bile ducts in the norm and with normal variants. Particular attention is paid to the influence of age and gender differences, as well as somatotypic factors on the size, volume and functional activity of the organs of the hepatobiliary complex. The article highlights the modern possibilities of ultrasound diagnostics as a leading non-invasive visualization method that allows assessing the structural and functional parameters of organs in dynamics, conducting early diagnostics of diseases and monitoring the effectiveness of therapy. The article provides data on normal ultrasound parameters, their variability, as well as criteria for assessing deviations, which is important in clinical practice. The relevance of further research aimed at improving the methods of individualized assessment of the hepatobiliary system, taking into account the constitutional characteristics of patients, is noted